2012
DOI: 10.1007/s10554-012-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrical and mechanical left atrial properties in patients with persistent atrial fibrillation

Abstract: The study of left atrial (LA) mechanical function during atrial fibrillation (AFib) can provide valuable information, particularly if such profiling is related to the cavity electrical substrate and conveys prognostic information. To assess if there is any relation between LA mechanical and electrical asynchrony and if such evaluation can be of interest in stratifying AFib patients. 50 patients with persistent AFib who underwent electrical cardioversion (CV) were evaluated with pre-CV atrial electrograms (AEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…24 In our study, we included more cases, and all of these cases had a clear diagnosis of LAAT (39 with LAAT vs 16 with sludge or LAAT). Furthermore, in contrast to other studies, 13,14 our analysis of LA synchronicity involved 2 apical chamber views and 12 segments for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In our study, we included more cases, and all of these cases had a clear diagnosis of LAAT (39 with LAAT vs 16 with sludge or LAAT). Furthermore, in contrast to other studies, 13,14 our analysis of LA synchronicity involved 2 apical chamber views and 12 segments for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Dispersed atrial mechanical activity is another interesting issue, especially in the context of documented interrelation between electrical asynchrony measured by atrial electrograms and mechanical asynchrony detected by 2DSTE . Most of the foregoing studies aimed to assess its significance in the predicting of sinus rhythm maintenance after direct current cardioversion or pulmonary veins isolation and to evaluate reverse remodeling after conversion into sinus rhythm . Asynchrony decreased in patients with AF after successful cardioversion and in patients with rheumatic mitral valve stenosis and sinus rhythm restoration after percutaneous treatment with balloon mitral valvuloplasty .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Zhijuan Shang et al, atrial dispersion was found increased in PAF patients compared to the healthy group and atrial dispersion was found out to be an independent predictor of AF development in patients with a normal left atrium size 24 . In another study; a high atrial dispersion before cardioversion was found decreased after cardioversion in patients, who were planned to undergo cardioversion because of AF 25,26 . In the study by Kupczynska et al, atrial dispersion was found out to be an independent predictor of thrombus formation in the left atrial appendage (LAA) in patients, in whom transesophageal echocardiography (TEE) was performed because of AF 27 .…”
Section: Resultsmentioning
confidence: 89%
“…In ASD patients the pathophysiological events related to PAF episodes were pre‐existent RA overload and device insertion, thus we studied RA dyssynchrony by determining the time‐to‐peak strain in the reservoir phase rather than during atrial contractile phase . RA pre‐closure strain, dyssynchrony, and volumetric parameters were significantly different compared to normal controls and associated with PAF.…”
Section: Discussionmentioning
confidence: 99%